2000
DOI: 10.1002/1096-8628(20001009)96:5<678::aid-ajmg15>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Long forms of the dopamine receptor (DRD4) gene VNTR are more prevalent in substance abusers: No interaction with functional alleles of the catechol-o-methyltransferase (COMT) gene

Abstract: Substance abuse is a complex behavior that is caused by both environmental and genetic factors. Work to understand the genetic factors has focused on genes related to dopamine activity because of its critical role in rewarding and reinforcing behaviors. The DRD3 and other dopamine receptor subtypes are expressed in many areas of the limbic system, and have been the objects of study for their possible roles in several neuropsychiatric disorders. Interest in variants of the D4 gene was heightened by reports that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 30 publications
1
29
1
Order By: Relevance
“…The DRD4P region contains two alleles, a long allele (L) and a short allele (S), with the length of the allele inversely associated with DRD4 transcription levels [34]. Alleles associated with a decrease in DRD4 activity in the prefrontal cortex have been associated with novelty seeking, attention deficit hyperactivity disorder, and substance abuse [35][37]. The effect of DRD4P on financial decisions has not been previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…The DRD4P region contains two alleles, a long allele (L) and a short allele (S), with the length of the allele inversely associated with DRD4 transcription levels [34]. Alleles associated with a decrease in DRD4 activity in the prefrontal cortex have been associated with novelty seeking, attention deficit hyperactivity disorder, and substance abuse [35][37]. The effect of DRD4P on financial decisions has not been previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…Faster metabolism results in reduced DA availability at the synapse, which reduces postsynaptic activation, inducing hypodopaminergic functioning. Generally, Vandenbergh et al [39] in 1997, and others [40] supported an association with the Val allele and Substance Use Disorder, but others did not [41]. Li et al [42] found the COMT rs737866 gene variants were independently associated with both novelty seeking (NS) and age of onset of drug use.…”
Section: Catecholamine-o-methyltransferase (Comt) Val158met Polymorphismmentioning
confidence: 99%
“…Variation in COMT may influence dopamine levels in the prefrontal cortex, leading to changes in cognition, affect, and reward processes, and may influence susceptibility to drug dependency (60). The high-activity 1947G allele is associated with an increased risk for methamphetamine abuse (61) and could potentially interact with DRD4 variant alleles to alter susceptibility to its use (62). The lower expression 1947A variant allele could have protective effects against smoking (63,64).…”
Section: Genes In Pathways Potentially Involved In Risk For Drug Depementioning
confidence: 99%